Using graphic editors when creating a single information space - Baidabekov Ауез; Yanishevskaya Анна; Fomin Алексей (Рroblems of engineering and professional education, 2023)
The article deals with the problems of using a graphic editor in creating a unified information space. A list of software products that work together with the graphic editor, are used in institutions or purchased. This article raises some issues that arise in the way of creating a unified information space.